Quantifying suspended sediment concentration in subglacial sediment plumes discharging from two Svalbard tidewater glaciers using Landsat-8 and in situ measurements - Schild, Kristin M.; Hawley, Robert L.; Chipman, Jonathan W.; Benn, Douglas I. (International Journal of Remote Sensing, 2017)
This work was supported by National Science Foundation IGERT award: [Grant Number DGE-0801490]; National Science Foundation GK-12 award: [Grant Number DGE-0947790]; NASA supplement award: [Grant Number NNX10AG22G]; American Alpine Club under their Research Grant; Geological Society of America under their Research Grant; the ConocoPhillips-Ludin Northern Area Program under the CRIOS project (Calving Rates and Impact on Sea Level); and Dartmouth Earth Sciences Department. Marine-terminating outlet glaciers discharge mass through iceberg calving, submarine melting, and meltwater run-off. While calving can be quantified by in situ and remote-sensing observations, meltwater run-off, the subglacial transport of meltwater, and submarine melting are not well constrained due to inherent difficulties observing the subglacial and proglacial environments at tidewater glaciers. Remote-sensing and in situ measurements of surface sediment plumes, and their suspended sediment concentration (SSC), have been used as a proxy for glacier meltwater run-off. However, this relationship between satellite reflectance and SSC has predominantly been established using land-terminating glaciers. Here, we use two Svalbard tidewater glaciers to establish a well-constrained relationship between Landsat-8 surface reflecance and SSC and argue that it can be used to measure relative meltwater run-off at tidewater glaciers throughout a summer melt season. We find the highest correlation between SSCs and Landsat-8 surface reflectance by using the red + NIR band combination (r2 = 0.76). The highest correlation between SSCs and in situ field spectrometer measurements is in the 740-800 nm wavelength range (r2 = 0.85), a spectral range not currently measured by Landsat. Additionally, we find that in situ and Landsat-8 measurements for surface reflectance of SSCs are not interchangeable and therefore establish a relationship for each detection method. We then use the Landsat-8 relationship to calculate total surface sediment load, finding a strong ...